2018
DOI: 10.1136/bmjgh-2017-000475
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of antibiotic-resistant wound infections from six countries in Africa

Abstract: IntroductionLittle is known about the antimicrobial susceptibility of common bacteria responsible for wound infections from many countries in sub-Saharan Africa.MethodsWe performed a retrospective review of microbial isolates collected based on clinical suspicion of wound infection between 2004 and 2016 from Mercy Ships, a non-governmental organisation operating a single mobile surgical unit in Benin, Congo, Liberia, Madagascar, Sierra Leone and Togo. Antimicrobial resistant organisms of interest were defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 12 publications
7
42
2
Order By: Relevance
“…Penicillins used in the current study. Such susceptibility pattern of these isolates is in agreement with other previous reports across Africa [30] . Multidrug resistance among Gram negative bacteria resistant to commonly used antimicrobials in wound infections is a serious concern [31,17] .…”
Section: Discussionsupporting
confidence: 93%
“…Penicillins used in the current study. Such susceptibility pattern of these isolates is in agreement with other previous reports across Africa [30] . Multidrug resistance among Gram negative bacteria resistant to commonly used antimicrobials in wound infections is a serious concern [31,17] .…”
Section: Discussionsupporting
confidence: 93%
“…Upreti and Shrestha in Nepal found the same rate of MRSA [28,29]. In a retrospective single center study conducted in 2016 by Mercy Ship during surgical outreaches in six sub-Saharan African countries (Benin,Togo, Liberia, Madagascar, Congo and Sierra-leone) Lai PS et al found the highest rates of MRSA in Benin (34.6%) and Congo (31.9%) and the lowest rate in Togo (14.3%) and Madagascar (14.5%) [30]. The difference in the rates of isolation of MRSA between studies may be due to different levels of inappropriate use of antibiotic but also to the effectiveness of hygiene programs.…”
Section: Discussionmentioning
confidence: 93%
“…Upreti et al have reported that 25% of E.coli and 40% of K. pneumoniae are ESBL producers. In 2016, Benin was found to have the highest rate of third generation cephalosporin resistant enterobacterales of six sub-Saharan African countries [30]. Almost all ESBL producers isolates showed co-resistance to other class of antibiotics such as aminoglycosides, quinolones, and trimethoprim-sulfamethoxazole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Buruli ulcers would need goal directed therapy with rifampicin/streptomycin and or surgical debridement and skin grafting, most ulcers are treated with over-the-counter available antibiotics. A study from Lai et al, who provided care on a ship, anchoring at six coastal West African countries, showed considerable resistance to common antibiotics (31). From clinical experiences at Masanga Hospital, a referral centre for patients with large wounds, it is known that most patients visited a traditional healer -and have started treatment (herbs and or antibiotics) -before seeking care in this rural hospital in Sierra Leone.…”
Section: Woundsmentioning
confidence: 99%